Asian Pacific phycology in the 21st century : prospects and challenges. Proceedings of the Second Asian Pacific Phycological Forum [Hongkong, China 21-25 June 1999] - Ang, Put O. Jr (Kluwer Academic Publishers, 2004)
Developments in hydrobiology ; v. 173